Kontribusi Pemikiran Imam Syafi'i terhadap Perkembangan Hukum Islam - Umar, Hasbi; Bafadhal, Husin; Adawiyah, Robiatul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study examines the contributions of Imam Syafi'i's thought to the development of Islamic law through a literature review approach. As the founder of the Shafi'i school of thought, he proposed a systematic legal methodology based on the Qur'an, Hadith, ijma' (consensus), and qiyas (analogy). Through his works such as Al-Umm and Ar-Risalah, he provided a practical legal framework that can be applied in various social and cultural contexts. The relevance of his thought remains alive in the contemporary era, enabling Islamic law to evolve and address modern challenges. This study highlights how Imam Syafi'i's thought serves as a widely recognized legal foundation and is applied in various legal systems in the Muslim world.